HIMMELFARB: O PAPEL DAS EMOÇÕES NO PROCESSO DE PERCEPÇÃO (CULTURAL) - Mathias, Dionei (Línguas & Letras, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->